En Route to Wide Area Emitting Organic Light‐Emitting Transistors for Intrinsic Drive‐Integrated Display Applications: A Comprehensive Review. (31st August 2021) - Ganesan, Paramaguru; Tsao, Hoi Nok; Gao, Peng
Abstract: Organic light‐emitting transistors (OLET) evolved from the fusion of the switching functionality of field‐effect transistors (FET) with the light‐emitting characteristics of organic light‐emitting diode (OLED) that can simplify the active‐matrix pixel device architecture and hence offer a promising pathway for future flat panel and flexible display technology. This review systematically analyzes the key device/molecular engineering tactics that assist in improving the electrode edge narrow emission to wide‐area emission for display applications via three different topics, that is, narrow to wide‐area emission, vertical architecture, and impact of high‐κ dielectric on the device performance. Source–drain electrode engineering such as symmetric/asymmetric, planar/non‐planar arrangement, semitransparent nature, multilayer approach comprising charge transport, and work function modification layers enable widening the emission zone. Vertical OLET architecture offers short channel lengths with a high aperture ratio, pixel type area emission, and stable light‐emitting area. Transistors utilizing high‐κ dielectric materials have assisted in lowering the operating voltage, enhancing luminance and air stability. The promising development in achieving wide‐area emission provides a solid basis for constructing OLET research toward display applications; however, it relies on developing highly luminescent and fast charge transporting materials, suitable semitransparent source/drain electrodes, high‐κ ‐dielectrics, and device architectural engineering. Abstract : The fusion of light‐emitting OLED technology with the switching functionality of OFET in a single device provokes a new research direction, organic light‐emitting transistors (OLET). This review summarizes the progress of OLET for their potential applications toward display technology via three promising tactics such as narrow to wide‐area emission, vertical architecture, and impact of high‐κ dielectrics.